Sulfur enhancement effects for uranium bioleaching in column reactors from a refractory uranium ore - Li, Qian; Yang, Yu; Ma, Jinfang; Sun, Jing; Li, Guangyue; Zhang, Ruiyong; Cui, Zhao; Li, Ting; Liu, Xiaobei (Frontiers in Microbiology, 2023)
The feasibility of sulfur enhancement for uranium bioleaching in column reactors was assessed with a designed mixed Acidithiobacillus ferrooxidans, Acidithiobacillus thiooxidans and Leptospirillum ferriphilum from a refractory uranium ore. The uranium extraction reached 86.2% with the sulfur enhancement (1 g/kg) in 77 days leaching process, increased by 12.6% versus the control without sulfur addition. The kinetic analysis showed that uranium bioleaching with sulfur enhancement in columns followed an internal diffusion through the product layer-controlled model. Ore residue characteristics indicated that sulfur enhancement could strengthen the porosity of passivation layer, improving the ore permeability. Notably, bacterial community analysis showed that sulfur enhancement at 1 g/kg could make the iron-oxidizing and sulfur-oxidizing bacteria on the ore surface maintain a good balance (approx. 1:1), and thus decomposing ore more effectively. Lastly, a possible mechanism model for uranium bioleaching with sulfur enhancement was proposed.